Pengaruh Penerapan Akuntansi Sektor Publik dan Kualitas Aparatur Pemerintah terhadap Pencegahan Fraud Laporan Keuangan (Studi Empiris pada Kota Pekalongan) - Sari, Fangela Myas; Safitri, Anni; Elshifa, Aria (Journal of Social and Policy Issues, 2024)
This study discusses how the application of public sector accounting and the quality of government officials in preventing financial reporting fraud in the Pekalongan city government and the purpose of this study is to examine how fraud prevention is influenced by organizational ethical behavior and internal control systems. BPK found a number of problems in cases of low quality financial reporting and non-compliance with statutory provisions. Methodology Approach, Design and Methodology Participants in this study consisted of OPD staff in Pekalongan City totaling 61 respondents and for the sample using Purposive sampling is a sampling technique, while direct surveys and questionnaire distribution are survey methods. Analysis with the Smart PLS Version 3.0 Application. Based on the research findings, the SAP implementation variables and the quality of government officials have a significant effect on preventing financial reporting fraud.